Sejarah Hukum Maritim Kerajaan Sriwijaya dan Majapahit dalam Hukum Indonesia Kini - Sartika Intaning Pradhani (Universitas Gadjah Mada, 2017)
The purpose of this research is to analyze the control of Sriwijaya and Majapahit Kingdom towards their maritime territory and to learn whether their control may be practiced in the regulatory on the maritime territory of Unitary State Republic of Indonesia today. It is a legal normative research which has descriptive and analytical nature. The control of Sriwijaya and Majapahit Kingdom towards their maritime territory was conducted through adat law. Maritime territory of Indonesia today is controlled by the written law created by the government and the unwritten law practiced by the people.